A new genus and species of family Mimarachnidae (Hemiptera: Fulgoromorpha: Fulgoroidae) from mid-Cretaceous Kachin amber, northern Myanmar. (November 2022) - He, Jia-hui; Jiang, Tian; Guan, Xin-er; Szwedo, Jacek
Abstract: A new planthopper genus Tenebricosus gen. nov. from mid-Cretaceous Kachin amber with its type species Tenebricosus coriaceus sp. nov. is described in the family Mimarachnidae. The new genus and species is the fourteenth genus and 22nd species of the extinct family Mimarachnidae, which is the most diverse planthopper family among Kachin amber inclusion. This genus can be distinguished from the preciously described genera in tegmen venation, with stem ScP + R shorter than the common stem ScP + R + MP, stem MP with two terminals in margin, costal cell broad and tegmen coriaceous with length/width ratio about 2.4. Diagnostic features of the new genus are briefly discussed.